2018
DOI: 10.1080/13696998.2018.1449751
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of barriers and facilitators in the use of health technology assessment in Colombia

Abstract: The study suggests that barriers and facilitators related to technical aspects of processing HTA reports and to the contact and interaction between researchers and policymakers had the greatest importance in Colombia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Of the 123 respondents who opened the questionnaire, 55 (45%) dropped out. This is comparable to previous studies, in which the drop-out rates were 72% 25 , 54% 26 , 42% 27 , and 30% 24 . Of those who dropped out, 19 completed the demographic section.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the 123 respondents who opened the questionnaire, 55 (45%) dropped out. This is comparable to previous studies, in which the drop-out rates were 72% 25 , 54% 26 , 42% 27 , and 30% 24 . Of those who dropped out, 19 completed the demographic section.…”
Section: Discussionsupporting
confidence: 90%
“…An initial list was identified via a scoping review completed for a comparable BWS study in the Netherlands 27 and verified for the Canadian setting. The same initial list was used as a point of departure for similar studies in Austria 24 , Colombia 25 and France, Germany, and the United Kingdom 26 . The list was translated into French by an independent translator in Canada and translation was verified by one of the study authors (MH).…”
Section: Identification Of Facilitators and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultural, social, legal, ethical, economic, technical, and medical criteria of an intervention in HTA should be examined, requiring special skills and competences [ 52 ]. In the curriculum of medical and pharmacy programs, there are some courses on the clinical aspect of technology, but other HTA skills have not been considered [ 53 ]. Developing and poor countries should work to minimize the costs of inappropriate decisions in the health sector; in doing so, one of their problems is allocating sufficient economic-financial resources to HTA.…”
Section: Discussionmentioning
confidence: 99%
“…For most low and middle-income countries, capacity building related to HTA is a major challenge, which hinders HTA on many levels [35,38,47]. For instance, it has been previously reported that a shortage of qualified personnel in Brazil compromises the methodological quality of HTA reports, resulting in a low number of reports finished in time [48].…”
Section: Discussionmentioning
confidence: 99%